Engagement and creation of professional identity in undergraduate nursing students: A convention-style orientation event - Burkhardt, M.; Gower, Shelley; Flavell, Helen; Taplin, John (2015)
Background: In an innovative event that challenged traditional orientation programs, the Curtin University School of Nursing and Midwifery brought together nursing students, academic and student support staff, and health industry representatives. This unique whole-of-school convention consisted of sessions tailored to each student year group and aimed to promote nursing identity, highlight leadership opportunities, and showcase employer pathways. Method: To evaluate the event, a survey approach was used to collect quantitative data via questionnaire and qualitative data via open-ended questions from first-year students (n = 113), staff (n = 24), and industry representatives (n = 14). Results: Students, staff, and industry evaluations indicated a successful event that achieved its goals, including student engagement and motivation and community building. Conclusion: This orientation model could be used as a basis for institution-wide engagement activities.